EFFECT OF DIFFERENT TYPES OF FERTILIZERS ON COTTON PHYTOMASS FORMATION (Experimental biology, 2023)
The values of organic and mineral fertilizers applied on cotton plantations cultivated on irrigated arable lands of gray soils of the Aravan region of the Kyrgyz Republic during the formation of the total cotton phytomass, in other words the more fertilizers are applied, the more cotton phytomass is produced, including root mass and after the harvest of raw cotton, a greater amount of post-harvest plant residues, the main bioenergy material, will enter the soil, serving to replenish soil organic matter.  Variants of the experiment with the use of the recommended doses of mineral fertilizers, as well as 1.5 and 0.5 norms, work to increase both the total phytomass and the yield of raw cotton, and their performance increases with an increase in the amount of mineral fertilizers.
Keywords: cotton, irrigated arable land, gray soils, mineral fertilizers, manure, winter green manure cotton-stalks, productivity, phytomass